A benzene alkylation catalyst and its preparation method and application

By introducing a cube cavity with a specific size distribution inside the crystals of the molecular sieve catalyst, the problem of long diffusion paths and low activity of existing catalysts in the benzene alkylation reaction is solved, and the catalyst activity, selectivity and stability are improved.

CN115869987BActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111138701.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-27
Publication Date
2025-03-04
Estimated Expiration
2041-09-27

AI Technical Summary

Technical Problem

The existing benzene alkylation catalysts have long diffusion paths and slow diffusion rates during the reaction, resulting in a decrease in catalyst activity, selectivity and shortening of life.

Method used

By introducing three size distributions of cube cavity inside the crystals of the molecular sieve catalyst, accounting for 55%-70%, 25%-35% and 5%-10% of the total cavity number, respectively, to improve the diffusion rate of the reaction molecules and the selectivity of the product.

Benefits of technology

It effectively improves the activity, selectivity and stability of the catalyst, slows down the rate of carbon deposits, extends the service life of the catalyst, and improves the conversion and selectivity of ethylbenzene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115869987B_ABST
    Figure CN115869987B_ABST
Patent Text Reader

Abstract

The present invention discloses a benzene alkylation catalyst and its preparation method and application. The catalyst is a molecular sieve catalyst, and the molecular sieve crystal contains three cubic cavities with different size distributions. The area distribution range of the rectangles corresponding to the vertical projections of the three cubic cavities from top to bottom is 30-80nm. 2 、350‑1000nm 2 and 1500‑3000nm 2 The proportions of the three types of cubic cavities to the total number of cavities are 55%-70%, 25%-35% and 5%-10% respectively. The catalyst of the present invention is used in the gas phase alkylation reaction of benzene and ethylene to produce ethylbenzene, which can significantly improve the ethylene conversion rate and selectivity and reduce the impurity content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic chemistry and chemical engineering, and in particular relates to a benzene alkylation catalyst and a preparation method and application thereof. Background Art

[0002] Benzene alkylation products, such as ethylbenzene, are important basic organic raw materials with a wide range of uses and play an important role in the development of the national economy. More than 90% of ethylbenzene is produced by the alkylation of benzene under the action of molecular sieve catalysts. According to the process conditions, benzene alkylation can be divided into gas phase method and liquid phase method.

[0003] The key technology of benzene alkylation is to develop a catalyst with high activity, high selectivity and high stability. The effective component of the catalyst is molecular sieve, which has a pure microporous structure. In the actual reaction process, there are problems such as long diffusion path and slow diffusion rate, which will lead to reduced activity, reduced selectivity and shortened life of the catalyst. Introducing cavities inside the microporous molecular sieve can effectively shorten the diffusion path of the reaction molecules, increase the diffusion rate of the reaction molecules, and the generated target product can also quickly diffuse out of the reaction system to avoid side reactions. It can also effectively inhibit the generation of heavy components and slow down the rate of carbon deposition, thereby greatly improving the activity, selectivity and stability of the catalyst.

[0004] CN 201410563714.3 discloses a MCM-22 molecular sieve with a cavity aggregation morphology and a preparation method thereof, wherein the molecular sieve has a size of 5-30 μm, the cavity wall is composed of MCM-22 small crystals of 20-200 nm, and the cavity wall thickness is 0.2-3.0 μm. The preparation method is as follows: (1) uniformly mixing an aluminum source, a silicon source, an alkali, water, polyethylene glycol, sodium lignin sulfonate and a template; (2) continuing to mix the mixture under the combined action of ultrasonic dispersion and mechanical stirring; (3) crystallizing the material obtained in step (2), and the product is washed, dried and roasted to obtain an MCM-22 molecular sieve with a cavity aggregation morphology. However, the molecular sieve cavity prepared by this method is not the true internal cavity of the molecular sieve crystal, but is obtained by aggregating and stacking small-grain MCM-22 molecular sieves, which belongs to the external cavity of the molecular sieve crystal. The external cavity of the crystal has little effect on improving the diffusion performance inside the molecular sieve crystal. In addition, the cavity morphology and size obtained by this method are irregular, which leads to a longer molecular diffusion path during the reaction and the catalytic performance of the molecular sieve is also affected accordingly.

[0005] CN 201110398881.3 discloses a method for preparing a hollow ZSM-5 nano zeolite, which mainly comprises the following steps: mixing a monodispersed ZSM-5 nano zeolite having a silicon-aluminum molar ratio of more than 20 and a particle size of 100-400nm with an alkaline substance aqueous solution having a concentration of 0.05-0.5mol / L, stirring at 80-200°C for 10h-200h, and separating. The ZSM-5 nano zeolite obtained by the method has a small number of cavities, a single cavity size, and a large single cavity size, which is not ideal for improving catalytic performance.

[0006] In summary, if it is possible to prepare cavities with specific morphology in molecular sieves, and the cavity size and number have an appropriate ratio combination, then the above-mentioned multiple problems can be solved at the same time, thereby improving the activity, selectivity and stability of the catalyst. Summary of the invention

[0007] The present invention aims to provide a benzene alkylation catalyst and a preparation method thereof and its application in benzene alkylation reaction, so as to further improve the activity, selectivity and stability of the benzene alkylation reaction catalyst.

[0008] The first aspect of the present invention is to provide a benzene alkylation catalyst, wherein the catalyst is a molecular sieve catalyst, wherein the molecular sieve crystal contains three cubic cavities of different sizes, wherein the rectangular areas corresponding to the vertical projections of the three cubic cavities from top to bottom are respectively in the range of 30-80 nm. 2 、350-1000nm 2 and 1500-3000nm 2 The proportions of the three types of cubic cavities to the total number of cavities are 55%-70%, 25%-35% and 5%-10% respectively.

[0009] In the above technical solution, preferably, the catalyst is a binder-free molecular sieve catalyst, preferably, the molecular sieve is a silicon-aluminum molecular sieve, and more preferably, the molecular sieve is a ZSM-5 molecular sieve.

[0010] In the above technical solution, preferably, the total specific surface area of ​​the catalyst is 450-700m 2 ·g -1 , with a total pore volume of 0.6-1.0 cm 3 ·g -1 .

[0011] In the above technical solution, preferably, the mechanical strength of the catalyst is 110-160 N / cm, and more preferably, the mechanical strength of the catalyst is 120-150 N / cm.

[0012] In the above technical solution, preferably, the bulk density of the catalyst is 0.5-0.55 g·cm -3 .

[0013] In the above technical solution, preferably, the SiO2 / Al2O3 molar ratio of the catalyst is 130-400.

[0014] The second aspect of the present invention is to provide a method for preparing a benzene alkylation catalyst, comprising the following steps:

[0015] (a) calcining the formed molecular sieve precursor in an air atmosphere at 250-400° C. for 2-5 hours to obtain a mixture E;

[0016] (b) The mixture E is contacted with a mixed organic base to obtain a mixture F, and the mixture F is treated at 150-220° C. for 4-24 hours, and then washed, dried and calcined to obtain a benzene alkylation catalyst.

[0017] In the above technical solution, preferably, in step (a), the calcination temperature and time are controlled so that the mass content of organic matter in the mixture E is 2wt.%-6wt.%, and the organic matter comes from the organic template in the molecular sieve synthesis raw material.

[0018] In the above technical solution, preferably, the mixed organic base in step (b) is an aqueous solution of the mixed organic base, and its mass concentration is 20%-30%.

[0019] In the above technical solution, preferably, the mass ratio of the mixed organic base aqueous solution and the mixture E in step (b) is (2-20):1.

[0020] In the above technical solution, preferably, the mixed organic base described in step (b) is a mixed aqueous solution of tetrapropylammonium hydroxide and other quaternary ammonium bases, and the other quaternary ammonium bases have the structural formula Wherein R1, R2, R3 and R4 are each independently selected from any one of n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, benzyl and phenethyl. R1, R2, R3 and R4 may be the same or different.

[0021] In the above technical solution, preferably, the other quaternary ammonium bases contain at least three different quaternary ammonium bases.

[0022] In the above technical solution, preferably, the mass ratio of tetrapropylammonium hydroxide to the total amount of other quaternary ammonium bases is (2-5):1.

[0023] In the above technical solution, preferably, the mass proportion of each quaternary ammonium base in other quaternary ammonium bases is 20%-60%.

[0024] In the above technical solution, preferably, the treatment process in step (b) is carried out in a closed space.

[0025] In the above technical solution, preferably, the washing, drying and roasting in step (b) can be carried out by any conventional method. For example, the washing can be carried out with deionized water until the pH value of the solution is 7-7.5; the drying temperature is 90-200°C and the drying time is 4-12 hours; the roasting temperature is 500-600°C and the roasting time is 4-8 hours.

[0026] In the above technical solution, preferably, the preparation process of the molecular sieve precursor in step (a) comprises the following steps:

[0027] (1) contacting a template, a silicon source, a first aluminum source, and water to obtain a mixture A;

[0028] The molar ratios of the template agent, silicon source, first aluminum source and water are respectively: template agent: silicon source = (0.1-1.0): 1; silicon source: first aluminum source = (130-400): 1, water: silicon source = (5-10): 1, wherein the silicon source is calculated as SiO2, and the first aluminum source is calculated as Al2O3;

[0029] (2) contacting mixture A, silicon powder and a second aluminum source to obtain mixture B;

[0030] The ratios of the mixture A, silicon powder and the second aluminum source are as follows: the weight ratio of the mixture A to the silicon powder is (0.2-0.8):1; the molar ratio of the silicon powder to the second aluminum source is (130-400):1; the silicon powder is calculated as SiO2, and the second aluminum source is calculated as Al2O3;

[0031] (3) forming the mixture B to obtain a mixture C;

[0032] (4) contacting the mixture C with an alkali source to obtain a molecular sieve precursor D;

[0033] The weight ratio of the alkali source to the mixture C is (1.5-10):1.

[0034] In the above technical scheme, preferably, the template agent described in step (1) is a mixture of tetrapropylammonium hydroxide and tetrapropylammonium bromide, and the molar ratio of tetrapropylammonium hydroxide to tetrapropylammonium bromide is (2-5):1; the silicon source is one or more of silica sol, white carbon black, and tetraethyl silicate; and the first aluminum source is one or more of aluminum chloride, aluminum nitrate, and aluminum sulfate.

[0035] In the above technical scheme, preferably, in step (1), the process of obtaining mixture A by contacting the template, the silicon source, the first aluminum source and water is: stirring the template, the silicon source, the first aluminum source and water in a closed container, the stirring time is 10h-24h, and the stirring temperature is 80-120°C.

[0036] In the above technical solution, preferably, in step (2), the second aluminum source is one or more of aluminum chloride, aluminum nitrate and aluminum sulfate.

[0037] In the above technical solution, preferably, in step (3), mixture B is formed to obtain mixture C. Mixture C can be made into strips as needed, and its cross-section is circular, gear-shaped, clover-shaped, four-leaf clover-shaped or honeycomb-shaped. The diameter of mixture C is 0.6-4.0 mm and the length is 2-10 mm.

[0038] In the above technical solution, preferably, the alkali source in step (4) is one or more of ammonia water, ethylamine, ethylenediamine, n-butylamine, hexamethylenediamine and cyclohexylamine;

[0039] In the above technical solution, preferably, in step (4), the process of contacting the mixture C with the alkali source to obtain the molecular sieve precursor D is: treating the mixture and the alkali source in a closed space at 150-220° C. for 24-96 hours. The treated product is preferably washed and dried.

[0040] The third aspect of the present invention is to provide an application of the above catalyst in the gas phase alkylation reaction of benzene and olefins.

[0041] In the above technical solution, preferably, the gas phase alkylation reaction is a reaction in which benzene and ethylene are alkylated to produce ethylbenzene, and the ethylene may be pure ethylene or other mixed gases containing ethylene.

[0042] In the above technical solution, preferably, the gas phase alkylation reaction conditions are as follows: reaction temperature is 300-400°C, pressure is 0.5-3.0MPa, ethylene mass space velocity is 0.1-10.0h -1 , the molar ratio of benzene to ethylene is 2-20.

[0043] The benzene alkylation catalyst provided by the present invention has the following beneficial effects:

[0044] 1. Research has found that diffusion performance plays a vital role in alkylation catalysts for ethylbenzene. For molecular sieve catalysts, if the molecular sieve crystals contain cavities of a specific size and proportion, the internal diffusion problem in the alkylation reaction can be effectively solved, the diffusion rate of the reaction molecules can be increased, and the conversion rate can be effectively improved. In addition, the generated target product can quickly diffuse out of the reaction system, inhibit the occurrence of side reactions, and improve the selectivity of the target product. At the same time, the rate of carbon deposition can be slowed down, and the service life of the catalyst can be increased.

[0045] 2. The catalyst of the present invention is preferably a binder-free catalyst, which does not contain any inert components, completely eliminating the negative effects of the inert components on the dilution of the active components of the molecular sieve and the clogging of the micropores of the molecular sieve, and further improving the activity, selectivity and stability of the catalyst in the alkylation reaction process of ethylbenzene.

[0046] 3. The catalyst of the present invention has the characteristics of high specific surface area, high pore volume, high mechanical strength and suitable bulk density, and is particularly suitable for industrial alkylation to produce ethylbenzene. In addition, the mixed organic base used in the present invention is cheap and easily available, and is suitable for large-scale industrial production.

[0047] 4. The catalyst of the present invention is used in the gas-phase alkylation of benzene and ethylene to produce ethylbenzene. Under the reaction conditions of a low molar ratio of benzene to ethylene, the ethylene conversion rate is greater than 99.9%, the ethyl selectivity in the alkylation product is greater than 99.8%, and the content of the key impurity xylene is below 350 ppm. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The XRD spectrum of the catalyst for producing ethylbenzene by gas-phase alkylation prepared in Example 1 of the present invention;

[0049] Figure 2 This is a TEM photo of the catalyst for producing ethylbenzene by gas-phase alkylation prepared in Example 1 of the present invention;

[0050] Figure 3 The XRD spectrum of the catalyst for producing ethylbenzene by gas-phase alkylation prepared in Example 2 of the present invention;

[0051] Figure 4 TEM photo of the catalyst prepared in Comparative Example 1;

[0052] Figure 5 This is the TEM photo of the catalyst prepared in Comparative Example 2. DETAILED DESCRIPTION

[0053] The present invention is described in detail below in conjunction with specific implementation modes, but it should be understood that the protection scope of the present invention is not limited by the specific implementation modes.

[0054] In the present invention, the cavity size and distribution of the catalyst for producing ethylbenzene by gas-phase alkylation are obtained by analyzing TEM photos; the total specific surface area and total pore volume are obtained by nitrogen adsorption and desorption test; the mechanical strength is obtained by using an intelligent particle strength tester; the SiO2 / Al2O3 molar ratio is obtained by ICP test, and the organic matter content in the mixture E is tested by a thermal analyzer.

[0055] In the present invention, the XRD spectrum of the catalyst was obtained by using the Ultima IV X-ray powder diffractometer produced by Rigaku Corporation of Japan. The voltage was selected as 35 kV, the current was selected as 30 mA, and the scanning speed was 1°·min -1 .

[0056] In the present invention, a G2F30 transmission electron microscope produced by FEI Company of the United States is used to obtain a TEM photograph of the catalyst. Before the test, the sample to be tested needs to be ground for 1-5 minutes, and then a large amount of ethanol is added to ultrasonically disperse it evenly. The suspension is added dropwise on a copper mesh, and the test can be carried out after the ethanol is completely evaporated.

[0057] In the present invention, the BEL-MAX specific surface and pore size analyzer produced by BELSORP of Japan is used to test the nitrogen adsorption and desorption isotherms of the catalyst at liquid nitrogen temperature, and the total specific surface area and total pore volume are calculated using the BET equation.

[0058] In the present invention, the mechanical strength of the catalyst is tested by using the DLIII intelligent particle strength tester of Dalian Penghui Technology Development Co., Ltd. The length of the tested catalyst is 5 mm and it is placed horizontally on the tester to test the maximum pressure the catalyst withstands when it is broken. After testing the crushing strength of 20 catalysts, the average value is taken.

[0059] In the present invention, the bulk density of the catalyst is measured using a 1000 ml graduated cylinder as the container, and the actual weight of the added catalyst (unit: g) is divided by the actual volume, and the unit is g·cm -3 .

[0060] In the present invention, Kontron Model S-35 ICP-AES analyzer is used to perform ICP testing to obtain silicon-to-aluminum ratio data.

[0061] In the present invention, TGA / DTA851 produced by Mettler-Toledo is used. e Thermal analyzer was used to test the organic content, with a heating rate of 10°C min -1 , the test temperature is 25℃ to 600℃, and the protective gas is N2.

[0062] [Example 1]

[0063] This embodiment is used to synthesize a benzene alkylation catalyst, and the specific preparation process is as follows: 135.6 grams of tetrapropylammonium hydroxide (aqueous solution with a concentration of 40wt%), 88.7 grams of tetrapropylammonium bromide, 60 grams of white carbon black, 2.14 grams of aluminum nitrate nonahydrate and 180 grams of water are mixed evenly, and stirred at 120°C for 10 hours in a closed container to obtain a mixture A1. 96 grams of the mixture A1, 120 grams of silicon powder and 3.81 grams of aluminum sulfate 18hydrate are contacted to obtain a mixture B1. B1 is extruded by adding an appropriate amount of deionized water to obtain a mixture C1 (the cross section of C1 is a four-leaf clover shape with a diameter of 1.2mm and a length of 3-8mm). 30 g of n-butylamine and 20 g of mixture C1 were treated at 220° C. for 24 hours in a closed space, then washed with deionized water until the pH value was 7.0, dried at 150° C. for 4 hours to obtain mixture D1, and mixture D1 was calcined at 250° C. for 5 hours in an air atmosphere to obtain mixture E1, in which the mass content of organic matter was 5.6 wt.%. 10 g of mixture E1 and 200 g of an organic base solution with a mass concentration of 20% (the solution contained four organic bases, tetrapropylammonium hydroxide, tetra-n-butylammonium hydroxide, mono-n-pentyltriphenylethylammonium hydroxide and di-n-hexyldiphenylmethylammonium hydroxide, and the mass proportions of the four were 80%, 10%, 5% and 5% respectively) were mixed uniformly to obtain mixture F1. Mixture F1 was treated at 220° C. for 24 hours in a closed space, then washed with deionized water until the pH value of the solution was 7.3, dried at 200° C. for 4 hours, and calcined at 600° C. for 4 hours to obtain benzene alkylation catalyst G1.

[0064] The XRD spectrum of benzene alkylation catalyst G1 is shown in Figure 1 As shown in Figure 1, the typical MFI topological structure diffraction peak is a ZSM-5 molecular sieve catalyst. The TEM image of benzene alkylation catalyst G1 is shown in Figure 1. Figure 2 As shown, the molecular sieve crystals in the catalyst contain cubic cavities of three sizes. The area distribution range of the rectangles corresponding to the vertical projections of the three cubic cavities from top to bottom is 35-75nm respectively. 2 、380-960nm 2 and 1800-2900nm 2 The proportions of the three types of cubic cavities are 61%, 32% and 7% respectively. Through testing, the total specific surface area of ​​benzene alkylation catalyst G1 is 560 m 2 ·g -1 , with a total pore volume of 0.8 cm 3 ·g -1 , mechanical strength is 145N / cm, bulk density is 0.52g·cm -3 The SiO2 / Al2O3 molar ratio of benzene alkylation catalyst G1 was 398 as determined by ICP testing.

[0065] [Example 2]

[0066] This embodiment is used to synthesize a benzene alkylation catalyst. The specific preparation process is as follows: 92.1 grams of tetrapropylammonium hydroxide (aqueous solution with a concentration of 40 wt%), 26.6 grams of tetrapropylammonium bromide, 60 grams of white carbon black, 3 grams of aluminum nitrate nonahydrate and 144 grams of water are mixed evenly, and stirred in a closed container at 100° C. for 20 hours to obtain a mixture A2. 60 grams of the mixture A2, 120 grams of silicon powder and 6 grams of aluminum nitrate nonahydrate are contacted to obtain a mixture B2. B2 is extruded by adding an appropriate amount of deionized water to obtain a mixture C2 (the cross section of C2 is gear-shaped, with a diameter of 1.5 mm and a length of 3-8 mm). 100 g of hexamethylenediamine and 20 g of mixture C2 were treated at 180° C. for 48 hours in a closed space, then washed with deionized water until the pH value was 7.0, and dried at 120° C. for 6 hours to obtain mixture D2. Mixture D2 was calcined at 300° C. for 4 hours in an air atmosphere to obtain mixture E2, in which the mass content of organic matter was 4.1 wt.%. 10 g of mixture E2 and 100 g of an organic base solution with a mass concentration of 25% (the solution contained five organic bases, namely tetrapropylammonium hydroxide, tetra-n-pentylammonium hydroxide, tetra-n-hexylammonium hydroxide, mono-n-pentyltriphenylethylammonium hydroxide and di-n-hexyldiphenylmethylammonium hydroxide, and the mass proportions of the five organic bases were 75%, 5%, 5%, 7.5% and 7.5% respectively) were mixed uniformly to obtain mixture F2. The mixture F2 was treated at 170° C. for 12 hours in a closed space, then washed with deionized water until the pH value of the solution was 7.1, dried at 150° C. for 8 hours, and calcined at 550° C. for 6 hours to obtain the benzene alkylation catalyst G2.

[0067] The XRD spectrum of benzene alkylation catalyst G2 is shown in Figure 3 As shown in the figure, the typical MFI topological structure diffraction peak is a ZSM-5 molecular sieve catalyst. The molecular sieve crystals in this catalyst contain cubic cavities of three sizes. The area distribution range of the rectangles corresponding to the vertical projections of these three cubic cavities from top to bottom is 35-55nm. 2 、500-780nm 2 and 1600-2200nm 2 The proportions of the three types of cubic cavities are 64%, 28% and 8% respectively. Through testing, the total specific surface area of ​​the benzene alkylation catalyst G2 is 560m 2 ·g -1 , the total pore volume is 0.82cm 3 ·g -1 , mechanical strength is 135N / cm, bulk density is 0.55g·cm -3 The SiO2 / Al2O3 molar ratio of benzene alkylation catalyst G2 was found to be 2:10 by ICP test.

[0068] [Example 3]

[0069] This embodiment is used to synthesize a benzene alkylation catalyst, and the specific preparation process is as follows: 135.6 grams of tetrapropylammonium hydroxide (aqueous solution with a concentration of 40wt%), 88.7 grams of tetrapropylammonium bromide, 60 grams of white carbon black, 2.14 grams of aluminum nitrate nonahydrate and 180 grams of water are mixed evenly, and stirred in a closed container at 120°C for 10 hours to obtain a mixture A3. 96 grams of the mixture A3, 120 grams of silicon powder and 3.81 grams of aluminum sulfate 18hydrate are contacted to obtain a mixture B3. B3 is extruded by adding an appropriate amount of deionized water to obtain a mixture C3 (the cross section of C3 is a four-leaf clover shape with a diameter of 1.2mm and a length of 3-8mm). 30 g of n-butylamine and 20 g of mixture C3 were treated at 220° C. for 24 hours in a closed space, then washed with deionized water until the pH value was 7.0, dried at 150° C. for 4 hours to obtain mixture D3, and mixture D3 was calcined at 400° C. for 2 hours in an air atmosphere to obtain mixture E3, in which the mass content of organic matter was 3.2 wt.%. 10 g of mixture E3 and 200 g of an organic base solution with a mass concentration of 20% (the solution contained four organic bases, tetrapropylammonium hydroxide, tetra-n-butylammonium hydroxide, mono-n-pentyltriphenylethylammonium hydroxide and di-n-hexyldiphenylmethylammonium hydroxide, and the mass proportions of the four were 80%, 10%, 5% and 5% respectively) were mixed uniformly to obtain mixture F3. Mixture F3 was treated at 220° C. for 24 hours in a closed space, then washed with deionized water until the pH value of the solution was 7.3, dried at 200° C. for 4 hours, and calcined at 600° C. for 4 hours to obtain benzene alkylation catalyst G3.

[0070] Benzene alkylation catalyst G3 has a typical MFI topological structure diffraction peak and is a ZSM-5 molecular sieve catalyst. The molecular sieve crystals in this catalyst contain cubic cavities of three sizes. The area distribution range of the rectangles corresponding to the vertical projections of these three cubic cavities from top to bottom is 50-80nm. 2 、550-1000nm 2 and 2500-3000nm 2 The proportions of the three types of cubic cavities are 55%, 35% and 10% respectively. Through testing, the total specific surface area of ​​the benzene alkylation catalyst G3 is 650m 2 ·g -1 , with a total pore volume of 0.9 cm 3 ·g -1 , mechanical strength is 135N / cm, bulk density is 0.53g·cm -3 The SiO2 / Al2O3 molar ratio of benzene alkylation catalyst G3 was 395 as determined by ICP testing.

[0071] [Example 4]

[0072] This embodiment is used to synthesize a benzene alkylation catalyst, and the specific preparation process is as follows: 135.6 grams of tetrapropylammonium hydroxide (aqueous solution with a concentration of 40 wt%), 88.7 grams of tetrapropylammonium bromide, 60 grams of white carbon black, 2.14 grams of aluminum nitrate nonahydrate and 180 grams of water are mixed evenly, and stirred at 120° C. for 10 hours in a closed container to obtain a mixture A4. 96 grams of the mixture A4, 120 grams of silicon powder and 3.81 grams of aluminum sulfate 18hydrate are contacted to obtain a mixture B4. B4 is extruded by adding an appropriate amount of deionized water to obtain a mixture C4 (the cross section of C4 is a four-leaf clover shape with a diameter of 1.2 mm and a length of 3-8 mm). 30 g of n-butylamine and 20 g of mixture C4 were treated at 220° C. for 24 hours in a closed space, then washed with deionized water until the pH value was 7.0, and dried at 150° C. for 4 hours to obtain mixture D4. Mixture D4 was calcined at 350° C. for 5 hours in an air atmosphere to obtain mixture E4, and the mass content of organic matter in mixture E4 was 3.6 wt.%. 10 g of mixture E4 and 200 g of an organic base solution with a mass concentration of 20% (the solution contained four organic bases, tetrapropylammonium hydroxide, tetra-n-butylammonium hydroxide, mono-n-pentyltriphenylethylammonium hydroxide and di-n-hexyldiphenylmethylammonium hydroxide, and the mass proportions of the four were 80%, 5%, 10% and 5% respectively) were mixed uniformly to obtain mixture F4. Mixture F4 was treated at 150° C. for 24 hours in a closed space, then washed with deionized water until the pH value of the solution was 7.3, dried at 200° C. for 4 hours, and calcined at 600° C. for 4 hours to obtain benzene alkylation catalyst G4.

[0073] Benzene alkylation catalyst G4 has a typical MFI topological structure diffraction peak and is a ZSM-5 molecular sieve catalyst. The molecular sieve crystals in this catalyst contain cubic cavities of three sizes. The area distribution range of the rectangles corresponding to the vertical projections of these three cubic cavities from top to bottom is 45-78nm respectively. 2 、350-820nm 2 and 1500-2200nm 2 The proportions of the three types of cubic cavities are 60%, 35% and 5% respectively. Through testing, the total specific surface area of ​​the benzene alkylation catalyst G4 is 680m 2 ·g -1 , with a total pore volume of 1.0 cm 3 ·g -1 , mechanical strength is 125N / cm, bulk density is 0.51g·cm -3 The SiO2 / Al2O3 molar ratio of benzene alkylation catalyst G4 was 393 as determined by ICP testing.

[0074] [Example 5]

[0075] This embodiment is used to synthesize a benzene alkylation catalyst. The specific preparation process is as follows: 135.6 grams of tetrapropylammonium hydroxide (aqueous solution with a concentration of 40 wt%), 88.7 grams of tetrapropylammonium bromide, 60 grams of white carbon black, 5.7 grams of aluminum nitrate nonahydrate and 180 grams of water are mixed evenly, and stirred in a closed container at 120° C. for 10 hours to obtain a mixture A5. 96 grams of the mixture A5, 120 grams of silicon powder and 10.16 grams of aluminum sulfate 18hydrate are contacted to obtain a mixture B5. B5 is added with an appropriate amount of deionized water and extruded to obtain a mixture C5 (the cross section of C5 is a four-leaf clover shape with a diameter of 1.2 mm and a length of 3-8 mm). 30 g of n-butylamine and 20 g of mixture C5 were treated at 220°C for 24 hours in a closed space, then washed with deionized water until the pH value was 7.0, dried at 150°C for 4 hours to obtain mixture D5, and mixture D5 was calcined at 250°C in an air atmosphere for 5 hours to obtain mixture E5, in which the mass content of organic matter was 5.6 wt.%. 10 g of mixture E5 and 200 g of an organic base solution with a mass concentration of 30% (the solution contained four organic bases, tetrapropylammonium hydroxide, tetra-n-butylammonium hydroxide, mono-n-pentyltriphenylethylammonium hydroxide and di-n-hexyldiphenylmethylammonium hydroxide, and the mass proportions of the four were 80%, 10%, 5% and 5% respectively) were mixed uniformly to obtain mixture F5. Mixture F5 was treated at 200°C for 8 hours in a closed space, then washed with deionized water until the pH value of the solution was 7.3, dried at 200°C for 4 hours and calcined at 600°C for 4 hours to obtain benzene alkylation catalyst G5.

[0076] Benzene alkylation catalyst G5 has a typical MFI topological structure diffraction peak and is a ZSM-5 molecular sieve catalyst. The molecular sieve crystals in this catalyst contain cubic cavities of three sizes. The area distribution range of the rectangles corresponding to the vertical projections of these three cubic cavities from top to bottom is 30-45nm respectively. 2 、360-560nm 2 and 1600-2800nm 2 The proportions of the three types of cubic cavities are 70%, 25% and 5% respectively. Through testing, the total specific surface area of ​​the benzene alkylation catalyst G5 is 470m 2 ·g -1 , with a total pore volume of 0.6 cm 3 ·g -1 , mechanical strength is 148N / cm, bulk density is 0.55g·cm -3 The SiO2 / Al2O3 molar ratio of benzene alkylation catalyst G5 was 138 as determined by ICP testing.

[0077] [Comparative Example 1]

[0078] Compared with Example 1, only the calcination temperature of the mixture D in step (a) is different, and the rest are the same. The specific preparation process is as follows: 135.6 grams of tetrapropylammonium hydroxide (aqueous solution with a concentration of 40wt%), 88.7 grams of tetrapropylammonium bromide, 60 grams of white carbon black, 2.14 grams of aluminum nitrate nonahydrate and 180 grams of water are mixed evenly, and stirred at 120°C for 10 hours in a sealed container to obtain a mixture a1. 96 grams of the mixture a1, 120 grams of silicon powder and 3.81 grams of aluminum sulfate 18hydrate are contacted to obtain a mixture b1. Add an appropriate amount of deionized water to b1 and extrude it to obtain a mixture c1 (the cross section of c1 is a four-leaf clover shape with a diameter of 1.2mm and a length of 3-8mm). 30 g of n-butylamine and 20 g of mixture c1 were treated at 220° C. for 24 hours in a closed space, then washed with deionized water until the pH value was 7.0, and dried at 150° C. for 4 hours to obtain mixture d1. Mixture d1 was calcined at 220° C. in an air atmosphere for 6 hours to obtain mixture e1, and the mass content of organic matter in mixture e1 was 8.5 wt.%. 10 g of mixture e1 and 200 g of an organic base solution with a mass concentration of 20% (the solution contained four organic bases, tetrapropylammonium hydroxide, tetra-n-butylammonium hydroxide, mono-n-pentyltriphenylethylammonium hydroxide and di-n-hexyldiphenylmethylammonium hydroxide, and the mass proportions of the four were 80%, 10%, 5% and 5% respectively) were mixed uniformly to obtain mixture f1. Mixture f1 was treated at 220° C. for 24 hours in a closed space, then washed with deionized water until the pH value of the solution was 7.3, dried at 200° C. for 4 hours, and calcined at 600° C. for 4 hours to obtain catalyst H1.

[0079] TEM image of catalyst H1 Figure 4 As shown in the figure, there is no obvious cubic cavity inside the catalyst crystal. Through testing, the total specific surface area of ​​catalyst H1 is 380m 2 ·g -1 , the total pore volume is 0.42 cm 3 ·g -1 , mechanical strength is 160N / cm, bulk density is 0.58g·cm -3 The SiO2 / Al2O3 molar ratio of catalyst H1 was 395 as determined by ICP testing.

[0080] [Comparative Example 2]

[0081] Compared with Example 1, only one organic base, dipropyl di-n-hexyl ammonium hydroxide, is added in addition to tetrapropyl ammonium hydroxide corresponding to the organic base in step (b), and the rest is the same. The specific preparation process is as follows: 135.6 grams of tetrapropyl ammonium hydroxide (aqueous solution with a concentration of 40wt%), 88.7 grams of tetrapropyl ammonium bromide, 60 grams of white carbon black, 2.14 grams of aluminum nitrate nonahydrate and 180 grams of water are mixed evenly, and stirred at 120°C for 10 hours in a closed container to obtain a mixture a2. 96 grams of the mixture a2, 120 grams of silicon powder and 3.81 grams of aluminum sulfate 18hydrate are contacted to obtain a mixture b2. B2 is extruded by adding an appropriate amount of deionized water to obtain a mixture c2 (the cross section of c2 is a four-leaf clover shape with a diameter of 1.2mm and a length of 3-8mm). 30 g of n-butylamine and 20 g of mixture c2 were treated at 220°C for 24 hours in a closed space, then washed with deionized water until the pH value was 7.0, dried at 150°C for 4 hours to obtain mixture d2, and mixture d2 was roasted at 250°C in an air atmosphere for 5 hours to obtain mixture e2, in which the mass content of organic matter was 5.6 wt.%. 10 g of mixture e2 and 200 g of an organic base solution with a mass concentration of 20% (the solution contained two organic bases, tetrapropylammonium hydroxide and dipropyl di-n-hexylammonium hydroxide, with the mass proportions of the two being 67% and 33%, respectively) were mixed uniformly to obtain mixture f2. Mixture f2 was treated at 220°C for 24 hours in a closed space, then washed with deionized water until the pH value of the solution was 7.3, dried at 200°C for 4 hours, and roasted at 600°C for 4 hours to obtain catalyst H2.

[0082] TEM image of catalyst H2 Figure 5 As shown, the cavities inside the molecular sieve crystals in the catalyst are irregular in shape, and the boundaries between adjacent cavities are unclear. The area and number of the irregular two-dimensional figures corresponding to the vertical projection of the cavities from top to bottom are obviously different from the claims of this patent. Through testing, the total specific surface area of ​​catalyst H2 is 520m 2 ·g -1 , with a total pore volume of 0.85 cm 3 ·g -1 , mechanical strength is 95N / cm, bulk density is 0.46g·cm -3 The SiO2 / Al2O3 molar ratio of the catalyst was 392 as determined by ICP.

[0083] [Example 6]

[0084] Catalysts G1-G2 and H1-H2 prepared in Examples 1-2 and Comparative Examples 1-2 were respectively applied to the gas phase alkylation of benzene and ethylene to produce ethylbenzene at a reaction temperature of 320°C, a pressure of 0.8 MPa, and an ethylene mass space velocity of 2.2 h -1, under the condition that the molar ratio of benzene to ethylene was 4.0, the ethylene conversion rate, ethyl selectivity and xylene content in the alkylation product were tested. The test results are shown in Table 1 below.

[0085] Table 1 Reaction results of gas phase alkylation of benzene and ethylene to produce ethylbenzene

[0086]

[0087] [Example 7]

[0088] The benzene alkylation catalysts G1-G2 and H1-H2 prepared in Examples 1-2 and Comparative Examples 1-2 were tested for their one-way life in the alkylation of benzene and ethylene to produce ethylbenzene under ultra-high ethylene mass space velocity reaction conditions. The specific test conditions are as follows: reaction temperature 400°C, pressure 3.5MPa, ethylene mass space velocity 5h -1 , the molar ratio of benzene to ethylene is 1.5, and the one-way life refers to the time from the start of the reaction to the time when the ethylene conversion rate drops to 60% of the initial conversion rate. The test results are shown in Table 2 below. Under ultra-high ethylene space velocity reaction conditions, the one-way life of G1-G2 is significantly longer than that of H1-H2.

[0089] Table 2 Single-pass life test results of catalysts under ultra-high space velocity reaction conditions

[0090] Catalyst No. One-way life, h G1 210 G2 232 H1 125 H2 118

[0091] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A benzene alkylation catalyst, characterized in that The catalyst is a binder-free molecular sieve catalyst, wherein the molecular sieve is a ZSM-5 molecular sieve; the molecular sieve crystal contains three cubic cavities with different size distributions, and the area distribution range of the rectangles corresponding to the vertical projections of the three cubic cavities from top to bottom is 30-80 nm. 2 、350-1000 nm 2 and 1500-3000 nm 2 The proportions of the three types of cubic cavities to the total number of cavities are 55%-70%, 25%-35% and 5%-10% respectively.

2. The catalyst according to claim 1, characterized in that The total specific surface area of ​​the catalyst is 450-700m 2 ·g -1 , with a total pore volume of 0.6-1.0 cm 3 ·g -1 .

3. The catalyst according to claim 1, characterized in that The mechanical strength of the catalyst is 110-160 N / cm.

4. The catalyst according to claim 1, characterized in that The mechanical strength of the catalyst is 120-150 N / cm.

5. The catalyst according to claim 1, characterized in that The bulk density of the catalyst is 0.5-0.55 g·cm -3 .

6. A method for preparing the benzene alkylation catalyst according to any one of claims 1 to 5, characterized in that: The steps include: (a) calcining the formed molecular sieve precursor in an air atmosphere at 250-400° C. for 2-5 hours to obtain a mixture E; (b) Mixture E is contacted with a mixed organic base to obtain mixture F, and mixture F is treated at 150-220°C for 4-24 hours, and then washed, dried and calcined to obtain a benzene alkylation catalyst.

7. The preparation method according to claim 6, characterized in that: In step (a), the calcination temperature and time are controlled so that the mass content of organic matter in the mixture E is 2 wt.%-6 wt.%.

8. The preparation method according to claim 6, characterized in that: The mixed organic base in step (b) is an aqueous solution of the mixed organic base, and its mass concentration is 20%-30%.

9. The preparation method according to claim 8, characterized in that: The mass ratio of the mixed organic base aqueous solution and the mixture E in step (b) is (2-20):

1.

10. The preparation method according to claim 6 or 8, characterized in that: The mixed organic base in step (b) is a mixed aqueous solution of tetrapropylammonium hydroxide and other quaternary ammonium bases, the structural formula of the other quaternary ammonium bases is , wherein R1, R2, R3 and R4 are each independently selected from any one of n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, benzyl and phenethyl.

11. The preparation method according to claim 10, characterized in that: The other quaternary ammonium bases contain at least three different quaternary ammonium bases.

12. The preparation method according to claim 10, characterized in that: The mass ratio of tetrapropylammonium hydroxide to the total amount of other quaternary ammonium bases is (2-5):

1.

13. The preparation method according to claim 10, characterized in that: The mass proportion of each quaternary ammonium base in other quaternary ammonium bases is 20%-60%.

14. The preparation method according to claim 6 or 7, characterized in that: The preparation process of the molecular sieve precursor in step (a) comprises the following steps: (1) contacting a template, a silicon source, a first aluminum source, and water to obtain a mixture A; The molar ratios of the template, silicon source, first aluminum source and water are respectively: template: silicon source = (0.1-1.0): 1; silicon source: first aluminum source = (130-400): 1, water: silicon source = (5-10): 1, wherein the silicon source is calculated as SiO2, and the first aluminum source is calculated as Al2O3; (2) contacting mixture A, silicon powder and a second aluminum source to obtain mixture B; The ratios of the mixture A, silicon powder and the second aluminum source are as follows: the weight ratio of the mixture A to the silicon powder is (0.2-0.8):1; the molar ratio of the silicon powder to the second aluminum source is (130-400):1; the silicon powder is calculated as SiO2, and the second aluminum source is calculated as Al2O3; (3) forming mixture B to obtain mixture C; (4) contacting the mixture C with an alkali source to obtain a molecular sieve precursor D; The weight ratio of the alkali source to the mixture C is (1.5-10):

1.

15. Use of the catalyst according to any one of claims 1 to 5 or the catalyst prepared by the method according to any one of claims 6 to 14 in the gas phase alkylation reaction of benzene with olefins.

Citation Information

Patent Citations

  • Method for preparing hollow zeolite socony mobil-5 (ZSM-5) nanometer zeolite

    CN102491366B

  • A kind of mcm-22 molecular sieve with cavity aggregation form and preparation method thereof

    CN105585023B

  • Hollow capsule nano ZSM-5 molecular sieve and preparation method thereof

    CN102674392A

  • Preparation method of catalyst used in process for preparing ethylbenzene by benzene-ethylene gas phase alkylation

    CN111744539A